(untitled) (Clinics, 2012)
OBJECTIVE: This study sought to compare the effects and outcomes of two ophthalmic viscosurgical devices, 1.6% hyaluronic acid/4.0% chondroitin sulfate and 2.0% hydroxypropylmethylcellulose, during phacoemulsification. METHODS: This prospective, randomized clinical trial comprised 78 eyes (39 patients) that received phacoemulsification performed by the same surgeon using a standardized technique. Patients were randomly assigned to receive either 1.6% hyaluronic acid/4.0% chondroitin sulfate or 2.0% hydroxypropylmethylcellulose on the first eye. The other eye was treated later and received the other viscoelastic agent. Preoperative and postoperative examinations (5, 24 and 48 hours; 7 and 14 days; 3 and 6 months) included measurements of the total volume of the ophthalmic viscosurgical device, ultrasound and washout times to completely remove the ophthalmic viscosurgical device, intraocular pressure, central corneal thickness and best-corrected visual acuity. The corneal endothelial cell count was measured at baseline and at six months postoperatively. ClinicalTrials.gov: NCT01387620. RESULTS: There were no statistically significant differences between groups in terms of cataract density or ultrasound time. However, it took longer to remove 2.0% hydroxypropylmethylcellulose than 1.6% hyaluronic acid/ 4.0% chondroitin sulfate, and the amount of viscoelastic material used was greater in the 2.0% hydroxypropylmethylcellulose group. In addition, the best-corrected visual acuity was significantly better in the hyaluronic acid/ chondroitin sulfate group, but this preferable outcome was only observed at 24 hours after the operation. There were no statistically significant differences between the two ophthalmic viscosurgical devices regarding the central corneal thickness or intraocular pressure measurements at any point in time. The corneal endothelial cell count was significantly higher in the hyaluronic acid/chondroitin sulfate group. CONCLUSION: The ophthalmic viscosurgical device consisting of 1.6% hyaluronic acid/4.0% chondroitin sulfate was more efficient during phacoemulsification and was easier to remove after IOL implantation than 2.0% hydroxypropylmethylcellulose. In addition, the corneal endothelial cell count was significantly higher following the use of hyaluronic acid/chondroitin sulfate than with hydroxypropylmethylcellulose, which promoted an improved level of corneal endothelium protection.